The correlation between serum fibroblast growth factor 19 and vascular calcification in maintenance hemodialysis patients - Yao Dan-dan; Ji Yun-long; Xue Qi; Qiu Fang-xin; Li Zuo-lin (Linchuang shenzangbing zazhi)
ObjectiveTo explore the correlation between serum fibroblast growth factor 19（FGF19） and vascular calcification in maintenance hemodialysis（MHD） patients， providing theoretical basis for an investigation the pathogenesis of vascular calcification in patients with dialysis.MethodThis was a cross-sectional study. A total of 80 MHD patients at the Department of Nephrology， Qingdao Chengyang People's Hospital， from January 1， 2022 to June 30， 2023 were enrolled. Chest and abdominal computed tomography （CT） scans were used to evaluate the vascular calcification. Based on the calcification of the aortic arch， thoracic aorta， abdominal aorta， and coronary artery， all participants were divided into the vascular calcification group（n=45） and non-vascular calcification group（n=35）. Clinical data and laboratory examinations between the two groups were collected and analyzed. Serum FGF19 levels were detected using enzyme-linked immunosorbent assay（ELISA）. Then， the correlation of FGF19 with serum phosphorus， and intact parathyroid hormone （iPTH） was studied. Further more， risk factor for vascular calcification development was performed using Logistic regression analysis.ResultsCompared with the non-vascular calcification group， the age （67.3 years vs. 56.4 years）， dialysis age （7.9 years vs. 3.4 years）， high sensitivity C-reactive protein （2.52×10-2 g/L vs. 1.32×10-2 g/L）， serum phosphorus （2.3 mmol/L vs.1.9 mmol/L）， iPTH （285.4×10-9 g/L vs. 185.4×10-9 g/L）， and alkaline phosphatase （136.4 g/L vs. 87.5 g/L） of patients with vascular calcification were significantly higher （P<0.05）. The serum FGF19 levels in patients with vascular calcification were significantly higher than those of the control group （105.4×10-9 g/L vs. 58.0×10-9 g/L，P<0.05）. There was a significant correlation of serum FGF19 level with serum phosphorus（r=0.235） and iPTH （r=0.201） （both P<0.05）. The results of Logistic regression analysis showed that longer dialysis age， higher serum phosphorus， higher iPTH， and higher FGF19 levels were independent risk factors for vascular calcification development in MHD patients（all P<0.05）.ConclusionThe serum FGF19 level is significantly elevated in hemodialysis patients with vascular calcification， which is an independent risk factor for vascular calcification development in hemodialysis patients. Thus， FGF19 may be an important factor mediating the development of vascular calcification.